Evaluation of a Group-Based Resilience Intervention for Typhoon Haiyan Survivors - Hechanova, Ma. Regina (Archīum Ateneo, 2016)
This study evaluated the impact of Katatagan, a culturally adapted, group-based, and mindfulness-informed resilience intervention developed for disaster survivors in the Philippines. The intervention aimed to teach six adaptive coping skills: harnessing strengths, managing physical reactions, managing thoughts and emotions, seeking solutions and support, identifying positive activities, and planning for the future. Pre- and post-intervention assessments were conducted with 163 Typhoon Haiyan survivors. Six-month follow-up assessments were obtained for 37 participants. Pre- and post-results showed improvements in participants’ self-efficacy on all six coping skills. The 6-month follow-up revealed significant improvements in four of the six coping skills. Focus group discussions conducted at follow-up revealed that mindfulness, self-care, strengths, and reframing were some of the topics that were most memorable to participants. Among these, participants identified mindfulness as a skill that they continued to use. Participants also shared that they felt stronger because of the intervention and have shared what they learned with others in their communities.